Quantifying the quality of predictions G3 model evaluation - Tkáčik, Marcel (2015)
Recent developments of New Keynesian models attracted many central banks to develop their own DSGE models for policy analysis and forecasting. The aim of this study is to evaluate the quality of the predictions made by the Czech National Bank which developed its own DSGE model and use it as the core forecasting model from July 2008. The quality of the predictions has been evaluted by comparing it with the Ministry of Finance of the Czech Republic and two commercial banks (Česká spořitelna and Komerční banka). Using the econometrical tests for the structural break and time series analysis, it has been concluded that the Czech National Bank experienced significant improvement in its prediction quality when employing the DSGE model, and surpassed the other three institutions. This study suggests that a well-specified DSGE model may enhance the prediction quality of key macroeconomic indicators compared to non-structural models and expert judgment.